Understanding the USMLE journey of Brazilian medical students and graduates: a narrative review - Garcia-Rosa, Beatriz S.; Urmenyi, Lucas G.; Santana, Gabriel C.; Marques, João Vitor M.; Miguez-Pinto, Joao P.; Ramalho, Clara; Boczar, Daniel; Andrade, Bruno B. (Frontiers in Medicine, 2024)
Over the past decades, advances in medical technology and research have promoted the globalization of medicine, drawing medical students and physicians worldwide into seeking for better career and financial prospects, as well as enhanced clinical and research training abroad.The medical landscape in Brazil has been marked by significant challenges over the past years, particularly within the Unified Health System (SUS). Despite the expansion of medical schools and initiatives such as the Mais Médicos program arising as efforts to improve healthcare access and decrease regional inequalities in the country, such problems as under-resourced working environments, inadequate infrastructure, and unattractive financial compensation for both physician and research careers, have risen as persisting challenges. In the pursuit of improved conditions, the United States Medical Licensing Examination (USMLE) has emerged as an increasingly common pathway for those seeking to overcome these challenges. This review explores the motivations behind Brazilians pursuing the USMLE whilst examining structural and financial challenges within the country's medical education and SUS landscape.